Free trade between the EU and Russia: Sectoral effects and impact on Northwest Russia - Ville Kaitila (The Research Institute of the Finnish Economy (ETLA), 2007)
We analyse the implications of free trade between the EU25 and Russia using GTAP, a computable general equilibrium model. We review the sectoral effects by countries and make a tentative assessment of the impact on the regions in northwest Russia. Free trade on its own would have a negative terms-of-trade effect in Russia and cause a small decline in welfare. If coupled with an increase in productivity, welfare would increase. This emphasises the importance of reforms in the Russian economy. The quantity of production in Russia in ferrous and non-ferrous metallurgy, machine building and metal working, and wood and paper are the principal declining sectors with free trade. Production in capital goods, fuel industry, and services increases. Thus there are some symptoms of Dutch disease. Due to its production structure the northwest would seem to benefit slightly less than Russia on average in terms of the volume of gross regional product. In this respect there are differences between the regions of northwest Russia.
Keywords: F15; F17; 330; EU; Russia; free trade; integration; Freihandelszone; Außenhandelseffekt; Wohlfahrtseffekt; Allgemeines Gleichgewicht; EU-Staaten; Russland; Russland (Nordwest)